Pulmonary embolism in patients with COVID-19: incidence, risk factors, clinical characteristics, and outcome. (24th June 2021) - Miró, Òscar; Jiménez, Sònia; Mebazaa, Alexandre; Freund, Yonathan; Burillo-Putze, Guillermo; Martín, Alfonso; Martín-Sánchez, Francisco Javier; García-Lamberechts, Eric Jorge; Alquézar-Arbé, Aitor; Jacob, Javier; Llorens, Pere; Piñera, Pascual; et al.
Abstract: Aims: We investigated the incidence, risk factors, clinical characteristics, and outcomes of pulmonary embolism (PE) in patients with COVID-19 attending emergency departments (EDs), before hospitalization. Methods and Results: We retrospectively reviewed all COVID-19 patients diagnosed with PE in 62 Spanish EDs (20% of Spanish EDs, case group) during the first COVID-19 outbreak. COVID-19 patients without PE and non-COVID-19 patients with PE were included as control groups. Adjusted comparisons for baseline characteristics, acute episode characteristics, and outcomes were made between cases and randomly selected controls (1:1 ratio). We identified 368 PE in 74 814 patients with COVID-19 attending EDs (4.92‰). The standardized incidence of PE in the COVID-19 population resulted in 310 per 100 000 person-years, significantly higher than that observed in the non-COVID-19 population [35 per 100 000 person-years; odds ratio (OR) 8.95 for PE in the COVID-19 population, 95% confidence interval (CI) 8.51–9.41]. Several characteristics in COVID-19 patients were independently associated with PE, the strongest being D-dimer >1000 ng/mL, and chest pain (direct association) and chronic heart failure (inverse association). COVID-19 patients with PE differed from non-COVID-19 patients with PE in 16 characteristics, most directly related to COVID-19 infection; remarkably, D-dimer >1000 ng/mL, leg swelling/pain, and PE risk factors were significantly less present. PE in COVID-19 patients affected smaller pulmonary arteries than in non-COVID-19 patients, although right ventricular dysfunction was similar in both groups. In-hospital mortality in cases (16.0%) was similar to COVID-19 patients without PE (16.6%; OR 0.96, 95% CI 0.65–1.42; and 11.4% in a subgroup of COVID-19 patients with PE ruled out by scanner, OR 1.48, 95% CI 0.97–2.27), but higher than in non-COVID-19 patients with PE (6.5%; OR 2.74, 95% CI 1.66–4.51). Adjustment for differences in baseline and acute episode characteristics and sensitivity analysis reported very similar associations. Conclusions: PE in COVID-19 patients at ED presentation is unusual (about 0.5%), but incidence is approximately ninefold higher than in the general (non-COVID-19) population. Moreover, risk factors and leg symptoms are less frequent, D-dimer increase is lower and emboli involve smaller pulmonary arteries. While PE probably does not increase the mortality of COVID-19 patients, mortality is higher in COVID-19 than in non-COVID-19 patients with PE. Graphical abstract: